Biosecurity assessment and critical improvement points of dairy cattle farms - Miroslav Kjosevski, Vanja Kondratenko, Branko Angjelovski, Aleksandar Janevski, Milenko Simovikj, Igor Djadjovski, Aleksandar Dodovski, Kiril Krstevski (University Ss Cyril and Methodius, Faculty of veterinary medicine, Lazar Pop – Trajkov 5-7, 1000 Skopje, Macedonia, 2022)
Farm biosecurity represents a combination of different measures implemented to reduce the risk of introduction and spread of disease agents. The type of biosecurity measures might differ a lot between the farming systems, even though the main goal is one, i.e., accomplishing high control of disease agents. Therefore, a biosecurity assessment based on the outputs of the implemented measures should objectively estimate the farm biosecurity level. Dairy farms in Macedonia are predominantly small scale with tie stall system under individual/family holdings. The risk of outbreaks and spreading of animal diseases will be significantly reduced if these farms have functional biosecurity plan. Therefore, the objective of this study was to assess the biosecurity level of dairy farms in Macedonia and to identify the critical points from the biosecurity perspective. The BIOCHECK CATTLE®protocol for Dairy cattle, including its scoring system, was used for the biosecurity assessment of the farms. Prior to the assessment, 16 national experts in the field rated this protocol for its reliability and applicability (by using the on-line survey). Out of 1000 randomly selected dairy farms in the country, the 952 farms were visited and 723 dairy farms were fully assessed and scored. According to the national experts, the lowest median regarding the importance of the questions in the survey was 7 (on a scale from 1-10) in 2% and the median of 10 and 9 was present in 92% of all questions. Regarding the scores of the performed on-farm assessment, the median of the total biosecurity score was 47, interquartile range (IR) of 39 – 56. The External Biosecurity was scored with median 70 (IR, 58-80), average of 67.7 ± 15.4, in opposite to the Internal Biosecurity which showed lower scores 24 (IR, 18-32), average of 26.4 ± 11.7, (p<0.0001). Within theexternal biosecurity the category with highest score was ‘Purchase and reproduction’ 84.0 ± 28.3 and the lowest scored category was ‘Transport and carcass removal’ 40.7± 28.3, (p<0.0001). In the internal biosecurity, the dairy farms shoved low ‘Health management’ 19.5± 20.0 which was significantly lower than the ‘Dairy management’ category 39.2± 19.1, (p<0.0001). In conclusion, the BIOCHECK CATTLE® survey is acceptable by the experts with some different priorities in the scores. The first conducted biosecurity assessment of dairy farms in Macedonia, indicated that the critical improvement points are the biosecurity risks related to ‘transport and carcass removal’ and the categories in the Internal biosecurity, especially health management.
Keywords: cattle farms, prevention, biosecurity, assessment, BIOCHECK®